PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PADA PEMERINTAH KOTA BENGKULU - Shinta, Seftya Dwi; Oktridarti, Levy (Universitas Prof.Hazairin,SH Bengkulu, 2022)
ABSTRACT The porpuse of this study is to find out the effect of human resource capacity, the utilization of information technology and accounting internal control for financial reporting information on the value of Bengkulu city government. The data used is primary data obtained from the results of questionnaires to the KK, BPM dan BPG Work Unit (SKPD) Bengkulu City Government. The samples used in the study were 55 respondents. Data analysis method used is multiple linear regression analysis. The research proves that the human resource capacity, utilization of information technology and accounting internal control positive effect on the value of financial reporting information to the government of Bengkulu